Strategies for reducing mismatch between demand and supply of grain legumes - REDDY, A AMARENDER (The Indian Journal of Agricultural Sciences, 2013)
The paper reviews the supply and demand situation of grain legumes (pulses and oilseeds with special reference togroundnut) and suggests strategies to decrease mismatch between supply and demand. If the current trends of production and demand continue, the likely deficit of grain legumes (both pulses and oilseeds) will increase significantly. There is a need to reduce the existing yield gaps between research station and farmers fields on the one hand and to invest in development of location specific high-yielding varieties with multiple-disease and pest resistant varieties to increase supply. There is a need for renewed focus on extension system with innovative seed systems to increase seed replacement ratio and variety replacement ratio. Finally, the paper comes out with crop and location specific strategies to meet the growing demand by 2020.